Iktomi and the boulder - Goble, Paul (New York Orchard Books, 1988)
Iktomi, a Plains Indian trickster, attempts to defeat a boulder with assistance of some bats, in this story which explains why the Great Plains are covered with small stones.
A Plains Indian story
520L
Keywords: Dakota Indians -- Legends; Indains of North America; Great Plain Legends